Interactive Media Development for Pancasila Education in Elementary Schools: Pengembangan Media Interaktif Pendidikan Pancasila di Sekolah Dasar - Feri Tirtoni; Tatia Lailatus Ramadhan (Academia Open, 2024)
General Background: The integration of interactive learning media has become essential in contemporary education to meet the demands of digital transformation and engage students more effectively. Specific Background: In SDN Sarirogo, low student performance in Pancasila Education, particularly regarding complex topics such as constitution and norms, highlights the need for innovative teaching approaches. Knowledge Gap: Existing instructional methods rely heavily on conventional techniques, such as lectures and textbook exercises, which fail to stimulate interest or cater to diverse learning styles. This has created a gap in effective engagement and comprehension of abstract concepts like constitutional principles and societal norms. Aims: This study aims to develop and evaluate interactive learning media using Macromedia Flash to enhance student understanding and interest in the subject matter. Results: Employing the ADDIE development model, the research yielded a highly effective product validated by media, design, and subject experts, achieving an average score of over 90% in expert evaluations. Field trials involving 30 students demonstrated a significant improvement in learning outcomes, with post-test scores markedly surpassing pre-test results. Novelty: Unlike prior approaches, this study leverages multimedia integration—combining audio, visual, animation, and interactive elements—to address diverse learning needs and provide an engaging platform for Pancasila Education. Implications: The findings underscore the potential of interactive learning media to transform traditional pedagogies, providing educators with tools to foster deeper understanding and sustained interest in constitutional and normative education. This approach not only supports curriculum goals within the Merdeka Belajar framework but also aligns with the broader vision of equipping students with foundational knowledge essential for civic engagement and societal harmony. Highlights: Innovative Approach: The study utilizes Macromedia Flash to create multimedia-rich educational content. Effective Results: Validations and field trials demonstrate over 90% effectiveness in improving student engagement and learning outcomes. Curriculum Alignment: Supports the Merdeka Belajar curriculum by integrating interactive media tailored to students' diverse learning styles. Keywords: Interactive Learning Media, Pancasila Education, Constitution and Norms, ADDIE Model, Merdeka Belajar